Diet, Microbiota, and Gut Permeability—The Unknown Triad in Rheumatoid Arthritis - Guerreiro, Catarina Sousa; Calado, Ângelo; Sousa, Joana; Fonseca, João Eurico (Frontiers in Medicine, 2018)
Growing experimental and clinical evidence suggests that a chronic inflammatory response induced by gut dysbiosis can critically contribute to the development of rheumatic diseases, including rheumatoid arthritis (RA). Of interest, an adherence to a Mediterranean diet has been linked to a reduction in mortality and morbidity in patients with inflammatory diseases. Diet and intestinal microbiota are modifying factors that may influence intestinal barrier strength, functional integrity and permeability regulation. Intestinal microbiota may play a crucial role in RA pathogenesis, but up to now no solid data has clarified a mechanistic relationship between gut microbiota and the development of RA. Nonetheless, microbiota composition in subjects with RA differs from that of controls and this altered microbiome can be partially restored after prescribing disease modifying antirheumatic drugs. High levels of Prevotella copri and similar species are correlated with low levels of microbiota previously associated with immune regulating properties. In addition, some nutrients can alter intestinal permeability and thereby influence the immune response without a known impact on the microbiota. However, critical questions remain to be elucidated, such as the way microbiome fluctuates in relation to diet, and how disease activity may be influenced by changes in diet, microbiota or diet-intestinal microbiota equilibrium.